2009
DOI: 10.1590/s1516-14392009000300012
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of sigma phase formation in a Duplex Stainless Steel

Abstract: This work determines the kinetics of sigma phase formation in UNS S31803 Duplex Stainless Steel (DSS), describing the phase transformations that occur in isothermal aging between 700 and 900 °C for time periods up to 1032 hours, allowing the determination of the Time-Temperature-Precipitation (TTP) diagram for sigma phase and proposing a model to predict the kinetics of sigma phase formation using a Johnson-Mehl-Avrami (JMA) type expression. The higher kinetics of sigma phase formation occurs at 850 °C. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
91
0
26

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(127 citation statements)
references
References 14 publications
10
91
0
26
Order By: Relevance
“…The kinetics of sigma formation measured in this study is consistent with that reported by Magnabosco 4 and with the results of Elmer et al 2 obtained using In-situ Synchrotron X-Ray Diffraction. More important than the kinetic measurements, however, is the indication that the Barkhausen noise signal can be adequately used to assess the decrease in ferromagnetic phase over time, thus making it a valuable non-destructive technique.…”
Section: Barkhausen Noise Measurementssupporting
confidence: 93%
See 1 more Smart Citation
“…The kinetics of sigma formation measured in this study is consistent with that reported by Magnabosco 4 and with the results of Elmer et al 2 obtained using In-situ Synchrotron X-Ray Diffraction. More important than the kinetic measurements, however, is the indication that the Barkhausen noise signal can be adequately used to assess the decrease in ferromagnetic phase over time, thus making it a valuable non-destructive technique.…”
Section: Barkhausen Noise Measurementssupporting
confidence: 93%
“…Since σ is the intermetallic phase more prominently formed during field applications of duplex stainless steel, its formation has been the object of several studies throughout the years, mostly focused on morphology and formation kinetics [1][2][3][4][5][6][7][8] , as well as its effects on mechanical properties [9][10][11] and corrosion resistance [12][13][14][15][16][17] . Processes that include high temperature thermal cycling, such as welding, are particularly critical regarding the appearance of σ, due to the temperature range to which the heat affected zone is exposed in a poorly controlled manner.…”
Section: Introductionmentioning
confidence: 99%
“…One physical method for determining the evolution of sigma phase is to measure magnetically the change in the volume fraction of ferrite [8].…”
Section: Introductionmentioning
confidence: 99%
“…Estas alterações metalúrgicas dizem respeito à precipitação de fases intermetálicas, como a fase sigma, que se presente, mesmo em pequenas quantidades, leva a efeitos deletérios em relação às propriedades Haskel et al mecânicas e de resistência à corrosão. Existem duas faixas de temperaturas que podem levar a precipitações nos aços inoxidáveis duplex, sendo elas a temperatura de 475 °C que é responsável pela precipitação da fase alfa linha (α') e a faixa de temperatura entre 600 e 900 °C na qual precipitam fases tais como a sigma (σ), chi (ϗ), austenita secundária (γ 2 ), carbetos tais como o M 7 C 3 e o M 23 C 6 e o nitreto Cr 2 N [5][6][7][8].…”
Section: Introductionunclassified